The curing behavior and properties of phthalonitrile resins using ionic liquids as a new class of curing agents - K. Cheng; J. B. Lv; J. Z. Ma; J. H. Hu; C. Chen; K. Zeng; G. Yang (eXPRESS Polymer Letters)
Binary blends composed of 1,3-bis (3,4-dicyanophenoxy) benzene (3BOCN) and ionic liquids (ILs) with different molecular structures were prepared. The curing behavior of these 3BOCN/ILs blends were studied by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and rheological analysis. The study suggested that the blends possessed a wide processing window and the structures of ILs (anion, cation and alkyl chain length at cation) had an effect on curing behavior. The 3BOCN/[EPy]BF4 resins were prepared at elevated temperature. IR spectra of the resins showed that there were triazine and isoindoline formed in curing process. The TGA and dynamic mechanical analysis (DMA) revealed that the resins have excellent thermal stability together with high storage modulus and high glass transition temperature (Tg). Dielectric properties, long term oxidative aging and water uptake measurements of the resins suggested the IL brought some unique properties to the resins.